Trends and factors influencing over-the-counter cold and cough medication sales in Guangzhou, China: 2011–2017 - Jian Chen; Daoze Wang; Jialu Zheng; Bing Zhang; Yilin Chen; Haoyu Long; Jinfeng Zeng; Zicheng Cao; Wenjie Han; Gang Wang; Xue Zhang; Jianyun Lu; et al. (BMC Infectious Diseases)
Abstract Background People are inclined to resort to Over-the-counter cold and cough medications (OTCCM) for self-treatment when experiencing upper respiratory tract infections, with consumption habits varying significantly among residents across different regions. Fluctuations in pharmacy OTCCM sales stem from numerous and intricate factors. However, most current studies predominantly examine the impact of singular factors on OTCCM volume. A comprehensive quantitative understanding of the evolving trends in OTCCM sales and the collective influence of multiple factors remains incomplete, particularly in subtropical mega-urban areas characterized by unique seasonal patterns of infectious diseases. Methods We monitored OTCCM sales at 36 stores of a major pharmaceutical chain in Guangzhou, China, from 2011 to 2017. We explored the association between OTCCM% and meteorological, infectious disease, and population movement factors using wavelet coherence and cross-correlation analysis. Extreme gradient boosting and SHapley Additive exPlanations were used to characterize each factor’s contributions. Results The OTCCM% in Guangzhou exhibited significant seasonal and annual cycles, with peaks occurring in the winter-spring and summer seasons. Meteorological factors, infectious disease factors, and OTCCM% were correlated within an annual cycle. OTCCM% had the highest correlation with the proportion of influenza-like illness at the same time or one week earlier during the winter-spring peaks. We revealed the contribution of infectious disease factors (38.15%), population movement factors (38.11%), and meteorological factors (23.74%) on OTCCM%, explicitly identifying the top three contributing factors as mobile population, influenza B, and mean temperature. The effect curve of mean temperature was reversed J-shaped, while the curves for relative humidity, sunshine duration, and outpatient visits were V-shaped. As influenza and other upper respiratory infections increased, OTCCM% showed an upward trend. Increased mobile population and in-migration index also contributed to the rise in OTCCM%. Conclusion This study comprehensively assesses the impact of meteorological, infectious disease, and population movement factors on OTCCM sales in a subtropical mega-city. These insights can inform local consumer behaviors and public health strategies, aid in business market forecasting, and support the allocation of medication resources and the prediction of disease outbreaks.